Combining simulation and optimization models on a production line problem: A case study - Vieira, António Amaro Costa (2019)
To improve the performance of a production line of a company of the Bosch Group, an optimization model was developed, which produces the optimum allocation of tasks to workstations and workers, according to a set of constraints. These results can thereafter be used in the simulation model, to estimate performance indicators, which would be difficult to estimate with other approaches, namely: waiting times, times spent with displacements and utilization rates. Thus, the purpose of this paper is twofold. First, it describes the combined use of the optimization and the simulation models. Thereafter, it presents the results obtained for 2 scenarios: one without displacements and another with displacements. The former was used to compare the simulation and the optimization models, whilst the later was used to assess the impact of displacements in the production line. By analyzing the results, it was possible to verify that the displacements increased the total time required to produce the devices in more than 10%. Furthermore, it was shown that the displacements caused considerable changes in the remaining performance indicators, indicating the relevance of considering them. This work also brings insights to the Industry 4.0 by proposing an approach to virtualize a production line system, providing the benefits of the 3D visualization of the simulation tool used in this research.